The Impact of Energy Prices on Precious Metals: A Comparison of the SARS-COV2 Period and Prior Period - Akbulaev, Nurkhodzha (International Journal of Energy Economics and Policy, 2023)
Commodities are defined as goods that are traded. Thousands of different items are sold on international markets, but strategically important commodities such as gold, silver, and oil are used far more frequently in the real estate industry and financial markets. Oil and these metals are employed in numerous industrial applications throughout the economy, but they also draw substantial investment. The purpose of this study is to investigate the causal connections between the prices of gold and silver, two precious metals, and oil and natural gas, the two most often used energy sources. This was accomplished by comparing the weekly prices of Brent Petroleum (BRENT), Crude Oil (WTI), Natural Gas (NG), and the weekly data of Gold and Silver during and before the SARS-CoV2 epidemic. The study employed the Distributed Delayed Autoregressive Bound Test (ARDL) approach to examine the relationship between the prices of energy (natural gas, Brent oil, and crude oil) and precious metals (silver and gold). The ARDL test showed that the prices of WTI, Brent, and NG had a big effect on the prices of silver and gold during and before the SARS-COV2 pandemic.